Eliciting expectation uncertainty from private households - Jonas Dovern (Humboldt University Berlin, 2023)
Recently, much attention has been devoted to the measurement of macroeconomic (expectation) uncertainty and its impact on aggregate economic fuctuations. This paper presents a new qualitative measure of macroeconomic expectation uncertainty based on data from a German online survey of consumer expectations. I document that the survey design works well. Elicited expectation uncertainty is related to data volatility and conventional measures of uncertainty as expected. Its dependency on socioeconomic factors is in line with previous evidence based on quantitative uncertainty measures. The new measure ofers a very efcient way of eliciting expectation uncertainty and can be used to obtain uncertainty measures on many diferent expectations at low cost.
urn:nbn:de:kobv:11-110-18452/26650-6
Keywords: D84; C83; 330; macroeconomic expectations; expectation uncertainty; density expectations